Reinduction of Hormone Sensitivity to Goserelin following Chemotherapy with Vinorelbine in Castration-Resistant Prostate Cancer - Tal Grenader; Anthony Goldberg (The Scientific World Journal)
Primary androgen ablation leads to symptomatic improvement and a reduction in prostate-specific antigen (PSA) serum levels in patients with advanced prostate cancer, but all patients eventually become refractory to hormone therapy with progression of the disease and a life expectancy of about a year. We describe a patient who developed castration resistance, was treated with vinorelbine, and continues to be progression free on therapy with luteinizing hormone releasing hormone agonists alone, more than 2.5 years following cessation of treatment with vinorelbine.